THE METHOD OF ROLL SURFACE QUALITY MEASUREMENT FOR CONTINUOUS HOT DIP ZINC COATED STEEL SHEET PRODUCTION LINE - Ki Yong Choi; Yu. A. Lebedinsky; E.I. Marukovich; A.M. Branovitsky; V.A. Dementev (Литьë и металлургия)
The present paper describes a developed analyzing system of roll surface during the process of continuous hot dip zinc coated steel sheet production line, in particular, adhering problem by transferred inclusions from roll to steel sheet surface during annealing process so called the pickup. The simulated test machine for coated roll surface in processing line has been designed and performed. The system makes it possible to analyze roll surface condition according to pickup phenomena from various roll coatings concerning operating conditions of hearth rolls in annealing furnace. The algorithm of fast pickup detection on surface is developed on the base of processing of several optical images of surface. The parameters for quality estimation of surface with pickups were developed. The optical system for images registration and image processing electronics may be used in real time and embed in processing line.